The Process of Knowledge and Transformation of Consciousness in the Era of the Internet - Mejevnikova Olga P. (International Journal on Orange Technologies, 2022)
The aim of the research is to reveal the peculiarities of the work of consciousness under the influence of information and communication technologies. The article describes the process of transformation of consciousness in virtual reality in the process of cognitive activity. The author tried to present the work of thinking in the context of the virtualization of modern society. Scientific novelty lies in the interdisciplinary consideration of the issue of virtualization of thinking with the involvement of the works of modern philosophers, sociologists, psychologists.